Laser Forming for Complex 3D Folding. Issue 10 (10th August 2017) - Lazarus, Nathan; Smith, Gabriel L.
Abstract: Laser heating to generate plastic strains for controlled bending, known as laser forming, is a promising technique for creating 3D structures based on origami‐inspired principles. Here, for the first time, laser cutting and forming are used to go from flat unpatterned metal sheet to final folded part, including up and down folds, all without manual handling. Folding direction is controlled by adjusting laser travel speed to create either a lateral or a vertical thermal gradient in the workpiece. Numerical modeling followed by experimental verification is used to determine the transition point between bending toward and away from the laser, followed by demonstration of a variety of complex 3D folded parts. Using this approach, laser forming is then used to precisely align two components, demonstrating the positioning of an optical reflector to guide the laser and pattern a portion of the sheeting originally inaccessible on the underside. All work here is done with a commercially available 20 W marking laser without modification. Abstract : Laser heating to generate plastic strains for controlled bending, known as laser forming, is a promising technique for creating 3D structures based on origami‐inspired principles. Here, for the first time, laser cutting and forming are used to go from flat unpatterned metal sheet to final folded part, including up and down folds, all without manual handling.